Motiv identitete v romanih Frančiška in Prijateljstvo pisatelja Fulvia Tomizze - Starc, Maja (Slavia Centralis, 2020)
THE MOTIF OF IDENTITY IN FULVIO TOMIZZA'S NOVELS FRANČIŠKA AND PRIJATELJSTVOThe motif of identity, especially border identity, has an important place in the novels of the writer Fulvio Tomizza, because as a border writer, as he called himself, it represents a leitmotif in his life and literary work. Because of his double identity the novels Prijateljstvo and Frančiška reveal his capacity of objective evaluation of groups of people who find themselves in a subordinate or superior position in certain circumstances. The discussion tries to show the writer's humane sense for people who find themselves in a minority position and his literary commitment to better relations between the Italian and Slovenian nation.
Keywords: border identity; Fulvio Tomizza; Prijateljstvo; Frančiška; minority